2020
DOI: 10.1007/s13369-020-04523-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Waste Cooking Oil and Waste Engine Oil Rejuvenated Asphalt Concrete Mixtures

Abstract: In road construction, different types of waste oil have been recommended to overcome the stiffening effect of reclaimed asphalt pavement content. However, the selection of an effective rejuvenator based on a comparative study can lead to using the resources more efficiently. In this study, waste cooking oil and waste engine oil are used to rejuvenate three different percentages (30%, 40%, and 50%) of reclaimed asphalt pavement following the current maximum industrial adaptability. The waste oil rejuvenated mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Moreover, the use of waste cooking oil is an eco-friendly solution due to its great performance as a rejuvenating agent [ 110 , 111 , 112 , 113 , 114 , 115 ]. Similarly, waste mineral oils can be reused as rejuvenators without further refinement [ 115 ], although vegetal oil-based rejuvenators usually require lower doses than the ones based on petroleum to achieve similar performance [ 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Another green option to produce rejuvenators is the use of organic waste to obtain bio-oil [ 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of waste cooking oil is an eco-friendly solution due to its great performance as a rejuvenating agent [ 110 , 111 , 112 , 113 , 114 , 115 ]. Similarly, waste mineral oils can be reused as rejuvenators without further refinement [ 115 ], although vegetal oil-based rejuvenators usually require lower doses than the ones based on petroleum to achieve similar performance [ 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. Another green option to produce rejuvenators is the use of organic waste to obtain bio-oil [ 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…The performance among the six mixtures based on the results obtained from this study is ranked from 1 to 6. For each test, the highest performance is ranked as 1, and the lowest is ranked as 6 [30]. For instance, the order of the ITS value for the alkaline immersion condition from best to the worst is PM-PL, PM-CR, FM-RA, FM-EA, CM, and FM-PA; therefore, they are ranked as 1 to 6 respectively.…”
Section: Overall Ranking Of the Mixturesmentioning
confidence: 99%
“…A structure's safe performance for the given life expectancy is dependent on increasing durability against water-induced damage. Some studies found that using RAP in combinations lowers moisture damage, whereas others found the opposite [16]. Durability is determined using the AASHTO T 245 standard -Standard Method of Test for Resistance to Plastic Flow of Asphalt Mixtures Using Marshall Apparatus.…”
Section: Technological Approachmentioning
confidence: 99%